Al-Ghazzali's Influence on Malay Thinkers: A Study of Shaykh 'Abd al-Samad al-Palimbani - Moris, Megawati (Islamic & Strategic Studies Institute (ISSI), 2016)
It is a widely-held claim that Abu> H{a>mid al-Ghazza>li>, popularly known as H{ujjat al-Isla>m, had a great and profound influence on the religious life and thought of the Malays. However, no in-depth and systematic study has been undertaken to demonstrate the extent of his influence. This study aims to fill this gap by attempting to show his influence on Malay thinkers of the eighteenth and nineteenth centuries through the medium of translations and commentaries of his works into Malay-Jawi. The text chosen to examine the influence of his teachings and the response of the Malay scholars is the Siyar al-sa>liki>n, a Malay rendition of the Mukhtas}ar ih}ya>’ ‘ulu>m al-di>n written by Shaykh ‘Abd al-S{amad al-Palimba>ni>. This study which utilized both methods of survey and textual analysis has shown that al-Ghazza>li>’s influence was present in the Malay world from the introduction of Islam to the nineteenth century in various forms and with varying degrees of intensity. This influence culminated during the period under study with the appearance of his works in Malay. These works consisted of literal translations and translations-cum-commentaries of al-Ghazza>li>’s basic books on Sufism. Malay works of the latter category have become larger and more comprehensive than their originals with the inclusion of teachings of other thinkers encompassing the tripartite sciences of the principles of religion (us}u>l al-di>n), jurisprudence (fiqh) and Sufism (tas}awwuf) within the framework of Ash‘arite theology, Sha>fi‘i> jurisprudence and Ghazzalian Sufism. An examination of the Siyar has shown that ‘Abd al-S{amad incorporated the Sufi doctrine of the seven degrees of the soul and the controversial metaphysical doctrine of the seven levels of Being derived from al-Burha>npu>ri> and accommodated them within the general framework of al-Ghazza>li>’s Sufism. These additions have made the Siyar a complete Malay text containing knowledge from jurisprudence to metaphysics. ‘Abd al-S{amad, by elucidating the doctrines in al-Ghazza>li>’s Ihya>’, the teachings on the soul and Ibn al-‘Arabi>’s metaphysics, also addressed the root problems of knowledge and orthodoxy faced by the Malay Muslim community during his time. From the findings derived from the analysis of the Siyar we can conclude that these Malay works are the agents for the transmission of al-Ghazza>li>’s perspectives and teachings with the dual purpose of educating as well as commenting on local issues and concerns. The Malay scholars led by ‘Abd al-S{amad have proven through their works, the depth of their understanding of al-Ghazza>li>’s teachings as well as their creativity and versatility in making this received knowledge relevant and useful.